Metaphor Identification Procedure and Its Application in Kurdish Political Speeches - Rozgar Y Omar; Himdad A Muhammad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Due to its ubiquity in our daily life, metaphor has been interlinked with various study fields. Nonetheless, the procedure to linguistic metaphor identification should be equally implemented in all these different areas. Such a procedure, termed Metaphor Identification Procedure (MIP), was designed by a number of scholars in 2007 and was revisited in 2010 and called Metaphor Identification Procedure Vrije Universiteit (MIPVU). Concerning this procedure in English, we have suggested two aspects to consider while identifying metaphors in discourse; one is in regard to a simplification of the procedure and the other is in respect of excluding some examples of personification when the sentence is in middle voice. Since its introduction to English, MIP(VU) has been applied in several other languages and adjustments have been proposed for these distinct languages. Hence, this paper attempts to apply MIP(VU) in Kurdish. Three recent presidential political speeches are analyzed. In light of some lexicographical and lexico-grammatical differences, adjustments have been suggested. Agreement among participants to the procedure and its adjustments is measured by Fleiss's kappa. At first, reliability of agreement among raters appeared to score "minimal". However, by assessing the cases of those who have closely worked on conceptual metaphor, kappa scores 0.71, which is interpreted as "moderate".